The Grolier Library of North American biographies (Grolier, 1994)
A collection of biographies of notable North Americans.
v. 1. Activists.--v. 2. Athletes.--v. 3. Enterpreneurs and inventors.--v. 4. Explorers.--v. 5. Performing artists.--v. 6. Political & military leaders.--v. 7. Scholars and educators.--v. 8. Scientists.--v. 9. Visual artists--v. 10. Writers.
Keywords: North American -- Biography; Biography